SYSTEMATIC LITERATURE REVIEW: ACCOUNTING INFORMATION SYSTEM, TAX RELAXATION, AND FINANCIAL PERFORMANCE OF MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMEs) - Sri Ayem; Reni Listyawati; Varda Samanta Adestia; Putri Syalsha Bilah Nasir; Wati Riadani; Yasminia Eka Rahmadani (Jurnal Akuntansi dan Pajak, 2023)
This study aims to provide a systematic literature review of the relationship between Accounting Information Systems (AIS), tax relaxation, and the financial performance of Micro, Small, and Medium Enterprises (MSMEs). The Systematic Literature Review (SLR) method was used in this study to examine previous research. The data analysis used in this study is in the form of 30 articles from 2020 to 2022 in the Google Scholar database. This study used 30 articles from the Google Scholar database from 2020 to 2022 for the data analysis. The findings demonstrated that the attribution theory is the theory that is utilized the most. According to the theory, a person's behavior is observed and its causes are explained by the person's actions. Utilizing or collecting additional journals and related recent articles is suggested for additional research to cover a broader understanding.